2020
DOI: 10.20944/preprints202004.0014.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Could Unconventional Immunomodulatory Agents Help Alleviate COVID-19 Symptoms and Severity?

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS coronavirus 2 or SARS-CoV2) is the cause of the respiratory infection known as COVID-19. From an immunopathological standpoint, coronaviruses such as SARS-CoV2 induce an increase in a variety of T-helper 1 (Th1) and inflammatory cytokines and chemokines including interleukins IL-1, IL-6, CCL2 protein and CXCL10 protein. In the absence of proven antiviral agents or an effective vaccine, substances with immunomodulatory activity may be able to inhibit inflamm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Considering these dysfunctions in patients with COVID-19, several studies and tests with drugs, traditionally used to control these changes, whether endocrine or metabolic, appear. Some adjuvant therapies for COVID-19 deserve special mention, such as immunomodulatory agents, immunoglobulin therapy, corticosteroids, and anticytokines used to control endocrine and metabolic changes( 9 , 52 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering these dysfunctions in patients with COVID-19, several studies and tests with drugs, traditionally used to control these changes, whether endocrine or metabolic, appear. Some adjuvant therapies for COVID-19 deserve special mention, such as immunomodulatory agents, immunoglobulin therapy, corticosteroids, and anticytokines used to control endocrine and metabolic changes( 9 , 52 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several initiatives for preventing and controlling non-communicable diseases have been adopted over the last decades, supported by the WHO. These initiatives are currently being tested in the treatment of COVID-19, especially in cases where obesity is also present (15,19,20) .…”
Section: Different Aspects Related To Obesity and The Covid-19 Pandemicmentioning
confidence: 99%
“…Considering these immune dysfunctions in patients with COVID-19, management therapies have used immunomodulatory drugs that benefit COVID-19 patients in pathways also altered by obesity (19,20) . Hoffmann et al (21) , demonstrated that SARS-CoV-2 uses the SARS-CoV angiotensin-converting enzyme (ACE) 2 receptor to enter the cells and transmembrane protease serine 2 (TMPRSS2) for spike (S) protein priming.…”
Section: Introductionmentioning
confidence: 99%
“…Using immunotherapy against this virus could also be an adequate option (Durán et al, 2019;Fávaro et al, 2019a;AminJafari and Ghasemi, 2020;Delafiori et al, 2020). It is known that coronavirus infection induces increased levels of T-helper 1 (Th1) cytokine, interferon (IFN)-gamma, inflammatory cytokines such as interleukins IL-1, IL-6 and IL-12, and connected cytokines and chemokines such as IL-8, chemokine (C-C motif) ligand 2 (CCL2 protein, also known as monocyte chemoattractant protein-1 or MCP-1) and C-X-C motif chemokine 10 (CXCL10 protein, named as interferon-γ, induced protein 10 or IP-10) (Mamber et al, 2020;Durán and Fávaro, 2020). The release of these cytokines moderated by these inflammatory and Th1 cytokines activate monocytes/macrophages and neutrophils account for immunopathological outcomes observed for this contamination type.…”
Section: Introductionmentioning
confidence: 99%
“…These hyper-inflammatory immune responses lead to increased Covid-19 severity and, consequently, to high mortality rates. Thus, it is possible saying that hyperinflammatory process inhibition is an unequivocal drug therapy alternative (Mamber et al, 2020;Zhong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%